Geomoprhologische Aspekte der Hochwasserkatastrophe im Juli 1972 auf den Philippinen - Stuckmann, Günther (ERDKUNDE, 1974)
The morphological effects of the July 1972 floods can be summed up as follows. As has been shown in part 1, there is strong erosion in the mountain area which borders the Central Luzon Plain. The geologically quick and considerable accumulation of the Central Luzon Plain shows this clearly. Man has intervened-for whatever reasons-in this very insecure natural equilibrium to such a degree that the consequence has been a great and accelerated erosion in the highlands. This process has been considerably activated in recent times by destroying or reducing the vegetation cover. The flood disaster of July 1972 was initially caused by considerably heightened precipitation. High runoff and considerable sediment loads in the rivers are the consequences of this. Only relatively insignificant sedimentation, which locally reaches larger scales and causes damage, was observed in the plain, as opposed to great erosion in the mountains. This year's flood gave rise to the highest economic loss of all floods so far, causing damage to the extent of 200 Mio. Pesos. These figures do not include consequential damage. The average annual damage caused by floods is estimated at 8,4 Mio. Pesos. The extent of the economic damage caused by the 1972 floods is certainly due to factors which are not only physio-geographical. Compared to preceding flood disasters other important reasons such as higher population density, improved infra structure, and more intensive cultivation of the arable land of the Central Luzon Plain have to be taken into account.